Low-loss resin composition, prepreg and copper clad laminate
By using a combination of components such as acetoene-p-vinyl biphenyl copolymer, a low loss resin composition with excellent dielectric properties, heat resistance and low expansion coefficient was prepared, which solved the problem of difficulty in preparing such resins in the prior art, and achieved the performance requirements of copper clad plate suitable for high-frequency and high-speed circuits.
Patent Information
- Application Number
- CN202411899070.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-23
AI Technical Summary
It is difficult to prepare low loss resin compositions with excellent dielectric properties, heat resistance and low coefficient of expansion, especially in high frequency and high speed circuit applications.
A low loss resin composition was prepared by prepolymerization and crosslinking reaction using a combination of acene-p-vinyl biphenyl copolymer, crosslinking agent, elastomer, initiator and filler, and a semi-cured sheet and copper-clad foil substrate were prepared by impregnation and hot pressing.
It achieves extremely low dielectric constant and dielectric loss, high heat resistance and low thermal expansion coefficient, and is suitable for copper clad applications in high-frequency and high-speed circuits.
Smart Images

Figure BDA0005202653120000061 
Figure BDA0005202653120000081 
Figure BDA0005202653120000082
Abstract
Description
Technical Field
[0001] The invention relates to the technology of copper foil substrate field, in particular to a low-loss resin composition, a prepreg and a copper foil clad substrate. Background Art
[0002] Copper clad laminates for high-frequency and high-speed circuits are mainly used in AI servers, high-speed network equipment, communications industry, and high-performance computing. As AI is widely used in all walks of life, the demand for computing power will grow exponentially, and the demand for AI servers will grow rapidly. The rapid growth of AI servers will drive the growth of demand for high-speed resins, and resins that can be used for high-speed copper clad laminates will have a large market growth in the future.
[0003] There are two mainstream resin composition process routes used for copper clad laminates for high-frequency and high-speed circuits with low loss level or above (substrate Df≤0.008): one is the process route composed of thermoplastic resin systems represented by PTFE; the other is the process route composed of thermosetting resin systems represented by hydrocarbon resins or modified polyphenylene ether resins. In the second process route composed of thermosetting resin systems, "PPO as the main body + cross-linking agent [the cross-linking agent can be bismaleimide resin, triallyl triisocyanate (TAIC), elastomer, etc.]" is currently the mainstream route. At the same time, the resin composition design technology for high-frequency and high-speed copper clad laminates has been continuously promoted in recent years and has developed into diversification. There have been process routes with modified maleimide (di- and multi-functional types) as the main resin; very low loss (Very Low Loss) levels composed of process routes of special epoxy resins (dicyclopentadiene type, diphenyl ether type, etc.) + benzoxazine resins, etc. Among them, Chinese patent CN117416106A discloses a new type of polymer resin for high-frequency and high-speed copper-clad laminates, which is prepared by acenaphthylene monomers, acenaphthylene as raw materials, heating, adding initiators, and reacting to obtain polyacenaphthylene resins, and prepregs are obtained by impregnating glass cloth with the resin. The copper-clad laminates obtained by the prepregs have excellent dielectric properties, and the dielectric constant is lower than that of the copper-clad laminates obtained by comparing the copper-clad laminates obtained by polyphenylene ether resins. However, the resin glue used for impregnation in the patent does not add fillers, and the glass transition temperature and expansion coefficient are not studied, and only the influence of the resin on the dielectric properties of the copper-clad laminates is mentioned; in addition, Chinese patent CN112368311A discloses a resin composition containing acenaphthylene compounds, which can maintain low dielectric properties well after water absorption treatment, but acenaphthylene is added in the form of monomers, which is easy to volatilize and will affect subsequent processing. In this regard, it is necessary to propose a new scheme to obtain a low-loss resin composition with excellent dielectric properties and high heat resistance and low expansion coefficient. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a low-loss resin composition, a prepreg and a copper-clad substrate, which have extremely low dielectric constants and dielectric losses, and have high heat resistance and low thermal expansion coefficient.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A low-loss resin composition comprises the following main components, by weight: 10-90 parts of acenaphthylene-p-vinyl biphenyl copolymer, 10-70 parts of a crosslinking agent, 20-60 parts of an elastomer, 0.1-3 parts of an initiator, and 10-90 parts of a filler; wherein the structural formula of the acenaphthylene-p-vinyl biphenyl copolymer is:
[0007] ; Wherein, m and n are the number of repeating units and are positive integers.
[0009] As a preferred embodiment, the preparation process of the acenaphthylene-p-vinyl biphenyl copolymer is as follows:
[0010] 1000g of acenaphthylene, 210g of p-divinylbiphenyl and 1200mL of toluene were placed in a 3000mL four-necked round-bottom flask equipped with a stirrer, a condenser, a thermometer and nitrogen protection while stirring. After acenaphthylene and p-divinylbiphenyl were completely dissolved, the mixture was heated to 70°C. After the solution in the flask stabilized at 70°C for 30 minutes, a 10% BPO toluene solution initiator was added using a peristaltic pump. The flow rate of the peristaltic pump was set so that 200g of the 10% BPO toluene solution was added dropwise within 6 hours. The temperature was maintained at 70°C for another 2h to complete the polymerization reaction and obtain an acenaphthylene-p-vinylbiphenyl copolymer.
[0011] As a preferred embodiment, the crosslinking agent is one or a combination of at least two of 1,2-bis(vinylphenyl)ethane, divinylbenzyl ether, divinylbenzene, divinylnaphthalene, divinylbiphenyl, tert-butylstyrene, triallyl isocyanurate, triallyl cyanurate, 1,2,4-trivinylcyclohexane, diallyl bisphenol A, styrene, butadiene, decadiene, octadiene, vinylcarbazole, and acrylate.
[0012] As a preferred embodiment, the crosslinking agent is 1,2-bis(vinylphenyl)ethane. 1,2-bis(p-vinylphenyl) contains multiple unsaturated double bonds and can react chemically with functional groups in the resin molecules to form covalent bonds, thereby converting linear or lightly branched macromolecules into a three-dimensional network structure, thereby improving the thermal stability, mechanical strength and chemical stability of the material.
[0013] As a preferred solution, the elastomer has a 1,2-vinyl structure and a styrene structure, and the mass of the 1,2-vinyl is 20%-90% of the mass of the elastomer, and the mass of the styrene is 10%-30% of the mass of the elastomer.
[0014] As a preferred embodiment, the initiator is one or a combination of at least two of diisopropylbenzene peroxide, tert-butyl perbenzoate, 2,5-di(2-ethylhexanoyl peroxy)-2,5-dimethylhexane, di-(tert-butyl peroxyisopropyl)benzene, (2,4-dichlorobenzoyl) peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, tert-butyl peroxy-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)-3-hexyne, 4,4-di(tert-butyl peroxy)butyl valerate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 3,3,5,7,7-pentamethyl-1,2,4-trioxepane, di-tert-butyl peroxide or tert-butyl peroxide isopropylbenzene.
[0015] As a preferred embodiment, the filler is one or a combination of at least two of crystalline silica, fused silica, spherical silica, hollow silica, glass powder, hollow glass microspheres, aluminum nitride, boron nitride, silicon carbide, silicon carbide aluminum, polytetrafluoroethylene powder, polyphenylene sulfide, polyetherimide, polyphenylene ether, and polyether sulfone powder.
[0016] A semi-cured sheet is prepared by dipping glass cloth into a glue solution formed by the aforementioned low-loss resin composition and then baking the glass cloth in an oven at 80-150°C for 1-20 minutes.
[0017] A copper-clad substrate is prepared by taking the aforementioned prepreg, covering the upper and lower surfaces with a copper foil respectively, putting it into a vacuum hot press, gradually heating it to 220°C, keeping the temperature and pressure for 80 minutes, and curing it to obtain the copper-clad substrate.
[0018] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0019] By prepolymerizing olefins and divinyl biphenyl to obtain an acenaphthylene-p-vinyl biphenyl copolymer with a certain molecular weight, less acenaphthylene monomer remains and is difficult to volatilize in the resin system. While maintaining good reaction activity, the resin system is prevented from curing too quickly to produce explosion polymerization. The subsequent cured product has high crosslinking density, good heat resistance, and a wide processing window, which is convenient for subsequent production and processing. In addition, the acenaphthylene structure has high symmetry and rigidity and does not contain elements such as oxygen, sulfur, and nitrogen, so that the resin composition has excellent dielectric properties and thermal properties and a low thermal expansion coefficient. In addition, the elastomer as its crosslinked curing matrix material can provide characteristics such as low dielectric constant, low dielectric loss and low water absorption, further improving the performance of the resin composition, so that the semi-cured sheet and copper-clad foil substrate prepared from the resin composition have extremely low dielectric constant and dielectric loss, high heat resistance and low expansion coefficient.
[0020] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. DETAILED DESCRIPTION
[0021] The present invention discloses a low-loss resin composition, which comprises the following main components by weight: 10-90 parts of acenaphthylene-p-vinyl biphenyl copolymer, 10-70 parts of a crosslinking agent, 20-60 parts of an elastomer, 0.1-3 parts of an initiator, and 10-90 parts of a filler; wherein the structural formula of the acenaphthylene-p-vinyl biphenyl copolymer is:
[0022] ; Wherein, m and n are the number of repeating units and are positive integers.
[0024] The preparation process of the acenaphthylene-p-vinyl biphenyl copolymer is as follows:
[0025] 1000g of acenaphthylene, 210g of p-divinylbiphenyl and 1200mL of toluene were placed in a 3000mL four-necked round-bottom flask equipped with a stirrer, a condenser, a thermometer and nitrogen protection while stirring. After acenaphthylene and p-divinylbiphenyl were completely dissolved, the mixture was heated to 70°C. After the solution in the flask was stabilized at 70°C for 30 minutes, a 10% BPO toluene solution initiator was added using a peristaltic pump. The flow rate of the peristaltic pump was set so that 200g of the 10% BPO toluene solution was added dropwise within 6 hours. The temperature was maintained at 70°C for another 2h to complete the polymerization reaction and obtain an acenaphthylene-p-vinylbiphenyl copolymer with a certain viscosity. The reaction process is shown below.
[0026]
[0027] The crosslinking agent is one or a combination of at least two of 1,2-bis(vinylphenyl)ethane, divinylbenzyl ether, divinylbenzene, divinylnaphthalene, divinylbiphenyl, tert-butylstyrene, triallyl isocyanurate, triallyl cyanurate, 1,2,4-trivinylcyclohexane, diallylbisphenol A, styrene, butadiene, decadiene, octadiene, vinylcarbazole, and acrylate. Preferably, 1,2-bis(vinylphenyl)ethane can be selected as the crosslinking agent. 1,2-bis(p-vinylphenyl) contains multiple unsaturated double bonds and can react chemically with functional groups in resin molecules to form covalent bonds, thereby converting linear or lightly branched macromolecules into three-dimensional network structures, thereby improving the thermal stability, mechanical strength, and chemical stability of the material.
[0028] Furthermore, the elastomer refers to a polymer having viscoelasticity that can impart toughness to the electronic material, so that the prepared electronic material has better toughness and lower dielectric constant, and the elastomer has unsaturated functional groups, and can undergo cross-linking reactions with other components having unsaturated functional groups, and the elastomer has a 1,2-vinyl structure and a styrene structure, and the mass of the 1,2-vinyl is 20%-90% of the mass of the elastomer, and the mass of styrene is 10%-30% of the mass of the elastomer. Specifically, examples of elastomers include but are not limited to polybutadiene, polyisoprene, and olefin copolymers such as styrene. The aforementioned elastomers can be used alone or in any combination, and polybutadiene is used herein.
[0029] The initiator is one or a combination of at least two of diisopropylbenzene peroxide, tert-butyl perbenzoate, 2,5-di(2-ethylhexanoyl peroxy)-2,5-dimethylhexane, di-(tert-butyl peroxyisopropyl)benzene, (2,4-dichlorobenzoyl)peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, tert-butyl peroxy-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)-3-hexyne, 4,4-di(tert-butyl peroxy)butyl valerate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 3,3,5,7,7-pentamethyl-1,2,4-trioxepane, di-tert-butyl peroxide or tert-butyl peroxide isopropylbenzene.
[0030] The fillers are all low dielectric fillers, and the low dielectric fillers include inorganic fillers and organic fillers. The inorganic fillers are one or a combination of at least two of crystalline silica, fused silica, spherical silica, hollow silica, glass powder, hollow glass microspheres, aluminum nitride, boron nitride, silicon carbide, and silicon carbide aluminum; the organic fillers are one or a combination of at least two of polytetrafluoroethylene powder, polyphenylene sulfide, polyetherimide, polyphenylene ether, and polyethersulfone powder. in addition, the present invention does not limit the shape and particle size of the inorganic filler, and the commonly used particle size is 0.01-50 μm, for example, 0.01 μm, 0.05 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm, etc.
[0031] The invention also discloses a semi-cured sheet, which is prepared by dipping glass cloth into a glue solution formed by the aforementioned low-loss resin composition and then baking the glass cloth in an oven at 80-150° C. for 1-20 minutes.
[0032] The present invention also discloses a copper-clad substrate. The aforementioned semi-cured sheet is covered with a copper foil on both the upper and lower surfaces, and placed in a vacuum hot press. The temperature is gradually raised to 220° C., and the temperature and pressure are maintained for 80 minutes, and the copper-clad substrate is cured.
[0033] The raw materials used in the following examples and comparative examples are shown in Table 1.
[0034]
[0035] The composition ratios of the embodiments and comparative examples in Table 1 are shown in Table 2.
[0036]
[0037] Table 2
[0038] The above multiple embodiments and comparative examples were subjected to performance tests, and the test methods were as follows:
[0039] Dielectric constant (Dk) and dielectric dissipation factor (Df) measurement
[0040] According to IPC TM 650 2.5.5.13 specification, the dielectric constant (Dk) and dielectric dissipation factor (Df) of the laminate are measured and calculated at an operating frequency of 10 GHz.
[0041] Glass transition temperature (Tg) test
[0042] The copper foil on both sides of the copper-clad substrate used for evaluation is removed by etching to obtain a non-clad board. The glass transition temperature (Tg) of the non-clad board is measured. Specifically, a dynamic mechanical analyzer (DMA) model "DMA850" manufactured by Waters (TA Instruments) is used to determine the Tg of the non-clad board. The test conditions are as follows: using a bending module, a frequency of 10 Hz, a heating rate of 3°C / min, and dynamic viscoelasticity is measured during the process of heating from room temperature to 280°C. Tg is the temperature at which tanδ reaches a maximum value in the obtained viscoelasticity curve.
[0043] Expansion coefficient α1
[0044] According to IPC-TM-650 2.4.24c, the copper-clad substrate used for evaluation was etched to remove the copper foil on both sides to obtain a non-clad board. The glass transition temperature (Tg) of the non-clad board was measured. Specifically, a TMA450 manufactured by TA Instruments was used. Thermomechanical Analyzer Thermomechanical analysis (TMA) was used to determine the expansion coefficient α1 of the unclad plate. The test conditions were as follows: using a compression module, the heating rate was 10°C / min, and the temperature was raised from room temperature to 280°C. α1 is the slope of the curve before the glass transition temperature.
[0045] Thermal stratification time
[0046] Tested in accordance with IPC-TM-650 2.4.9. Using TA Instruments Model "TMA450" Thermomechanical Analyzer Thermomechanical analysis (TMA) was used to determine the Tg of the unclad plate. The test conditions were as follows: using a compression module, the heating rate was 10°C / min, the temperature was raised from room temperature to 288°C, and the temperature was kept for 60 minutes. If the curve had a significant mutation, it was judged as delamination and the time was recorded.
[0047] The test results are shown in Table 3.
[0048]
[0049] Table 3
[0050] The above data are analyzed. It can be seen from Examples 1-6 that the resin composition of the present invention has a higher glass transition temperature, a lower thermal expansion coefficient, an extremely low dielectric constant and dielectric loss, and better heat resistance. At the same time, it can be seen that the higher the content of acenaphthylene-p-vinyl biphenyl copolymer, the higher the glass transition temperature and the lower the thermal expansion coefficient; specifically, compared with Example 1, Example 3, Example 3 and Example 6, Example 4, Example 4, and Example 6, under the same other conditions, the glass transition temperature, dielectric properties, expansion coefficient and heat resistance of the resin composition with acenaphthylene-p-vinyl biphenyl copolymer as the main body in the present invention application are better than the resin composition with polyacenaphthylene resin or acenaphthylene as the main body; in addition, compared with Example 1 and Example 2, and compared with Comparative Example 1 and Comparative Example 2, different elastomers with different mass fractions of 1,2-vinyl are selected. The elastomer selected in Example 1 is 1, The mass fraction of 2-vinyl is 80%, and the mass fraction of 1,2-vinyl in the elastomer of Example 2 is 70%, but there is no obvious difference in performance between Example 1 and Example 2. It can be seen that within a certain range, the mass fraction of 1,2-vinyl in the elastomer will not have a significant impact on the resin system. Combined with Example 5 for comparison, the proportion of cross-linking agent in Example 5 is increased, and the proportion of elastomer is reduced. Its Tg is significantly improved compared with the other two examples, and the expansion coefficient is reduced. It can be seen that the increase in the proportion of cross-linking agent can effectively increase the Tg of the resin composition and reduce the expansion coefficient of the resin composition; on the other hand, the proportion of elastomer in Comparative Example 1 and Comparative Example 3 is increased, and the Tg and expansion coefficient decrease significantly, but the dielectric properties and heat resistance are improved.
[0051] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A low-loss resin composition, characterized in that: The main components are as follows, by weight: 10-90 parts of acenaphthylene-p-vinyl biphenyl copolymer, 10-70 parts of a crosslinking agent, 20-60 parts of an elastomer, 0.1-3 parts of an initiator, and 10-90 parts of a filler; wherein the structural formula of the acenaphthylene-p-vinyl biphenyl copolymer is: ; Wherein, m and n are the number of repeating units and are positive integers.
2. The low-loss resin composition according to claim 1, characterized in that: The preparation process of the acenaphthylene-p-vinyl biphenyl copolymer is as follows: 1000g of acenaphthylene, 210g of p-divinylbiphenyl and 1200mL of toluene were placed in a 3000mL four-necked round-bottom flask equipped with a stirrer, a condenser, a thermometer and nitrogen protection while stirring. After acenaphthylene and p-divinylbiphenyl were completely dissolved, the mixture was heated to 70°C. After the solution in the flask stabilized at 70°C for 30 minutes, a 10% BPO toluene solution initiator was added using a peristaltic pump. The flow rate of the peristaltic pump was set so that 200g of the 10% BPO toluene solution was added dropwise within 6 hours. The temperature was maintained at 70°C for another 2h to complete the polymerization reaction and obtain an acenaphthylene-p-vinylbiphenyl copolymer.
3. The low-loss resin composition according to claim 1, characterized in that: The crosslinking agent is one or a combination of at least two of 1,2-bis(vinylphenyl)ethane, divinylbenzyl ether, divinylbenzene, divinylnaphthalene, divinylbiphenyl, tert-butylstyrene, triallyl isocyanurate, triallyl cyanurate, 1,2,4-trivinylcyclohexane, diallyl bisphenol A, styrene, butadiene, decadiene, octadiene, vinylcarbazole, and acrylate.
4. The low-loss resin composition according to claim 3, characterized in that: The crosslinking agent is 1,2-bis(vinylphenyl)ethane.
5. The low-loss resin composition according to claim 1, characterized in that: The elastomer has a 1,2-vinyl structure and a styrene structure, wherein the mass of the 1,2-vinyl is 20%-90% of the mass of the elastomer, and the mass of the styrene is 10%-30% of the mass of the elastomer.
6. The low-loss resin composition according to claim 1, characterized in that: The initiator is one or a combination of at least two of diisopropylbenzene peroxide, tert-butyl perbenzoate, 2,5-di(2-ethylhexanoyl peroxy)-2,5-dimethylhexane, di-(tert-butyl peroxyisopropyl)benzene, (2,4-dichlorobenzoyl)peroxide, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)hexane, tert-butyl peroxy-2-ethylhexyl carbonate, 2,5-dimethyl-2,5-bis(tert-butyl peroxy)-3-hexyne, 4,4-di(tert-butyl peroxy)butyl valerate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 3,3,5,7,7-pentamethyl-1,2,4-trioxepane, di-tert-butyl peroxide or tert-butyl peroxide isopropylbenzene.
7. The low-loss resin composition according to claim 1, characterized in that: The filler is one or a combination of at least two of crystalline silica, fused silica, spherical silica, hollow silica, glass powder, hollow glass microspheres, aluminum nitride, boron nitride, silicon carbide, silicon carbide aluminum, polytetrafluoroethylene powder, polyphenylene sulfide, polyetherimide, polyphenylene ether, and polyether sulfone powder.
8. A prepreg, characterized in that: The glass cloth is immersed in a glue solution formed by the low-loss resin composition according to any one of claims 1 to 7, and then baked in an oven at 80 to 150° C. for 1 to 20 minutes.
9. A copper-clad substrate, characterized in that: Take the semi-cured sheet as described in claim 8, cover the upper and lower surfaces with a copper foil respectively, put it into a vacuum hot press, gradually heat it to 220°C, keep it at this temperature and pressure for 80 minutes, and cure it to obtain a copper-clad substrate.
Citation Information
Patent Citations
Resin composition, prepreg, film with resin, metal foil with resin, metal-clad laminate and wiring board
CN112368311A
Novel polymer resin for high-frequency and high-speed copper-clad plate
CN117416106A
Thermosetting resin composition, prepreg produced by using thermosetting resin composition, and metal foil clad laminate
CN109385020A
Novel polymer resin for high-frequency and high-speed copper-clad plates
CN113320245A
Prepreg, metal-clad laminate, and wiring board
CN113574102A
Cited By
High-speed low-expansion-coefficient resin composition containing unsaturated hydrocarbon resin and application thereof
CN121471448A
High speed low expansion resin composition containing unsaturated hydrocarbon resin and its use
CN121471448B
Resin composition, prepreg and application of prepreg in rigid-flex printed circuit board
CN121517885A
Low dielectric fluorene-based copolymer resin for m9 copper clad plate and its atp controllable preparation method
CN122628275A